2015
DOI: 10.3389/fvets.2015.00072
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Emergency Vaccination Having Played a Crucial Role to Control the 1965/66 Foot-and-Mouth Disease Outbreak in Switzerland

Abstract: Foot-and-mouth disease (FMD) is a highly contagious disease that caused several large outbreaks in Europe in the last century. The last important outbreak in Switzerland took place in 1965/66 and affected more than 900 premises and more than 50,000 animals were slaughtered. Large-scale emergency vaccination of the cattle and pig population has been applied to control the epidemic. In recent years, many studies have used infectious disease models to assess the impact of different disease control measures, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Real-life data (i.e., empirical outbreak data) is needed to fully execute this process. To our knowledge, few models in veterinary science have been externally validated (59)(60)(61). This is usually due to the high associated costs or ethics of obtaining such data, and the complexity of the modeled systems.…”
Section: Post-programming Stage Model Verification and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-life data (i.e., empirical outbreak data) is needed to fully execute this process. To our knowledge, few models in veterinary science have been externally validated (59)(60)(61). This is usually due to the high associated costs or ethics of obtaining such data, and the complexity of the modeled systems.…”
Section: Post-programming Stage Model Verification and Validationmentioning
confidence: 99%
“…If empirical outbreak data are lacking from the setting in which the model was built and applied-such as in the case of exotic diseases and regions with historical disease freedom-then validation options might include either adapting the model to a region where data are available, or using previous outbreak data. For example, historical data from the last Swiss FMD outbreak was used to validate a current FMD model for Switzerland (61). FIGURE 4 | Line plots illustrating the effect of varying the transmission rate, β, on the number of susceptible (S) and infected (I) animals in a stochastic model with SI disease dynamics.…”
Section: Post-programming Stage Model Verification and Validationmentioning
confidence: 99%
“…The Davis Animal Disease Simulation (DADS) model is a stochastic, spatial simulation model to simulate the spread and evaluate the alternative mitigation strategies for FMD control in a designated geographical area [ 27 , 32 ]. It has been used to estimate FMD spread [ 69 , 70 ], examine epidemic and economic impacts [ 71 ], evaluate mitigation strategies [ 33 , 72 , 73 ], evaluate the effect of animal movement tracing [ 74 ], and examine the importance of stochasticity and modifying the assumption of homogeneous mixing [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various modelling studies have shown that certain vaccination strategies may offer a benefit over standard stamping out (SO) approaches for FMD control and eradication in non-endemic countries [5][6][7][8][9]. Analyses of the recent, large-scale epidemics of FMD that occurred in Korea [10] and Japan [11] concluded that early adoption of vaccination enhanced the speed of disease control and eradication attempts.…”
Section: Introductionmentioning
confidence: 99%